Brain pericytes are the most thrombin-sensitive matrix metalloproteinase-9-releasing cell type constituting the blood–brain barrier in vitro. (10th July 2015) - Machida, Takashi; Takata, Fuyuko; Matsumoto, Junichi; Takenoshita, Hisayo; Kimura, Ikuya; Yamauchi, Atsushi; Dohgu, Shinya; Kataoka, Yasufumi
Highlights: Thrombin induced MMP-9 release from brain pericytes. This MMP-9 release from pericytes was higher than that from other BBB cells. Pericytes expressed high and moderate levels of PAR1 and PAR4 mRNA, respectively. PAR1 inhibitor blocked the thrombin-induced MMP-9 release from pericytes. Thrombin-PAR1/PAR4 axis in pericytes may mediate ICH-associated BBB disruption. Abstract: In the acute phase of intracerebral hemorrhage (ICH), hemorrhagic transformation and brain edema are associated with blood–brain barrier (BBB) disruption. Elevated levels of thrombin, a coagulation factor, contribute to the development of brain edema during ICH through matrix metalloproteinase (MMP)-9 production. Thrombin directly induces a variety of cellular responses through its specific receptors known as protease-activated receptors (PARs). However, it remains unclear which cell types constituting the BBB mainly produce MMP-9 in response to thrombin. Here, we compared the MMP-9 release induced by thrombin using primary cultures of rat brain microvascular endothelial cells, astrocytes, and pericytes. Brain pericytes exhibited the highest levels of MMP-9 release due to thrombin stimulation among the BBB cells. The pattern of PAR mRNA expression in pericytes was characterized by high expression of PAR1 and moderate expression of PAR4. Heat-inactivated thrombin failed to stimulate pericytes to release MMP-9. A selective PAR1 inhibitor SCH79797 blocked the thrombin-induced MMP-9 release from pericytes. These findings suggest that both PAR1 and PAR4 mediate thrombin-induced MMP-9 release from pericytes. The present study raises the possibility that brain pericytes could play a pivotal role as a highly thrombin-sensitive and MMP-9-producing cell type at the BBB in brain damage including ICH.